Contribution of Digital Literacy to Students' Science Learning Outcomes in Online Learning - Akhyar, Yundri; Fitri, Anggi; Zalisman, Zalisman; Syarif, Muhammad Ilham; Niswah, Niswah; Simbolon, Parlindungan; Purnamasari S, Ayu; Tryana, Nofita; Abidin, Zaitun (International Journal of Elementary Education, 2021)
Online learning has a negative impact on students, especially students who cannot use online learning support facilities. This has an impact on the decline in the quality of student learning outcomes. This study aims to analyze the effect of implementing digital literacy on students' science learning outcomes in online learning during the Covid-19 pandemic. This research is research in the field of education using a quantitative approach and correlation method. The population in this study amounted to 348 people. Determination of the sample in this study using the random sampling technique. The data collection methods used are questionnaires and science learning outcomes tests. The instrument used has gone through the stages of testing the validity and reliability of the instrument. The data analysis used in this research is simple linear regression analysis, which previously carried out several analysis prerequisite tests in the form of normality and homogeneity tests. The results showed that the calculation of the correlation coefficient of 4.412 is greater than 2.034 with a significance value of 0.000 less than an alpha value of 0.05, a coefficient of determination of 0.371 x 100% of 37.1%. Based on these results, it can be concluded that there is a positive and significant effect on the application of digital literacy on students' science learning outcomes.